2010
DOI: 10.1073/pnas.1002758107
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cells derived from mouse models of lysosomal storage disorders

Abstract: Most lysosomal storage diseases (LSDs) are life-threatening genetic diseases. The pathogenesis of these diseases is poorly understood. Induced pluripotent stem (iPS) cell technology offers new opportunities for both mechanistic studies and development of stem cellbased therapies. Here we report the generation of disease-specific iPS cells from mouse models of Fabry disease, globoid cell leukodystrophy (GLD), and mucopolysaccharidosis VII (MPSVII). These mouse model-derived iPS cells showed defects in disease-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 33 publications
2
26
2
Order By: Relevance
“…Most iPS cells derived from human [12, 15, 16, 35, 38, 44, 57, 58] or murine [8, 14, 27, 35, 44, 53, 58, 59] origin. It has been shown that iPS cells can be generated from a variety of cell types, which differ in terms of mutational burden, relicative potential in vitro, availability, accessibility, and reprogramming efficiency.…”
Section: Sources Of Somatic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most iPS cells derived from human [12, 15, 16, 35, 38, 44, 57, 58] or murine [8, 14, 27, 35, 44, 53, 58, 59] origin. It has been shown that iPS cells can be generated from a variety of cell types, which differ in terms of mutational burden, relicative potential in vitro, availability, accessibility, and reprogramming efficiency.…”
Section: Sources Of Somatic Cellsmentioning
confidence: 99%
“…It is associated with severe multisystem abnormalities including cardiac hypertrophy and stroke. Meng et al [59] investigated the generation and characterization of iPS cells from mouse models of Fabry disease.…”
Section: Modeling Cardiac Disease Using Patient-specific Ips Cellsmentioning
confidence: 99%
“…Recently iPS cells from several mouse models of lysosomal storage disorders have been described, 40 but induction of iPS cells from human cells has been reported to date for only one human lysosomal storage disorder, type III Gaucher disease. 27 There are Ն 2 potential critical advantages of HSC derivation from genetically corrected iPS cells instead of gene correction of autologous HSCs.…”
Section: Differentiating Ips Cells In Mps Ih 843mentioning
confidence: 99%
“…The ability to obtain stem cells specific to an individual offers new prospects for regenerative medicine in general, and also open a door for autologous stem cell-based gene therapy in neuropathic MPS in particular. In fact, generation of murine iPS cells tailored to MPS VII mouse has been reported using primary MPS VII fibroblasts isolated from tail-clips [70]. While this new class of stem cells may provide opportunities to develop patient-specific pluripotent cell lines for cell-based CNS therapies, substantial research and developments are still required for their ultimate usage in clinics.…”
Section: Cell-based Brain Injectionmentioning
confidence: 99%